Anticonvulsant and anxiolyic activities of ethyl acetate fraction of Cassia fistula Linn. pods in mice - Kalaiyarasi, Chinnasamy; Karthika, Kalivaradhan; Ragupathi, Govindharaj; Saravanan, Sampath (Pharmacognosy Communications)
Cassia fistula L. (Leguminacea) is used by Indian and Tanzanian traditional healers for treating various ailments related to the central nervous system. Aims: The present study aimed to evaluate the anticonvulsant and anxiolytic activity of the ethyl acetate fraction obtained from a hydroalcoholic extraction of Cassia fistula pods (EAFCF) and thereby to provide scientific validation for its traditional use. Methods: Preliminary phytochemical analysis and estimation of the flavonoid content of the ethyl acetate fraction was performed. Anticonvulsant activity was assessed by the subcutaneous pentylenetetrazole test (s.c. PTZ test). Anxiolytic activity was assessed by elevated plus maze (EPM) and open field tests (OFT). The sedative and motor toxicity was evaluated by a phenobarbitone induced sleep test and rotarod behavior respectively. Results: Photochemical analysis revealed the presence of a high flavanoid content in the ethyl acetate fraction. Treatment of EAFCF (50 and 100 mg/kg) significantly increased the latency to the onset of minimal clonic seizure and generalized tonic clonic seizure and animals were completely protected from death due to PTZ administration. Administration of EAFCF at the dose of 100 mg/kg markedly increased the open arm entries and time spent in open arm in EPM. In OFT, EAFCF increased the number of central squares crossed and time spent in the central compartment. EAFCF in the doses used in this experiment did not produce sedation or motor toxicity. Conclusion: The results obtained herein clearly indicate the anticonvulsant and anxiolytic activity of EAFCF which may be due to the high flavonoid content. These findings give the scientific support for common use of this plant for treating epilepsy and anxiety.
Keywords: Pentylenetetrazole; elevated plus maze; thigmotaxic behaviour; flavonoid content estimation; Cassia fistula; neurobehavioral profile